Child Criminalization (Case Study of Decision No. 1270/pid.B/2022/PN.Maros) - Muhammad Ashadul; Muhammad Fauzi Ramadhan; Airlangga Putera (Faculty of Law, Universitas Muslim Indonesia, 2025)
This research aims to analyze the process of criminalizing children and actions against delinquent children at the Maros District Court, as well as the obstacles faced in its implementation. The research method used was qualitative with interview and documentation techniques at the Maros District Court and the Maros Class II State Detention Center. The research results reveal that the implementation of Law no. 11 of 2012 Juncto Law no. 3 of 1979 concerning the Juvenile Court in Maros Prison has considered the statements of witnesses and victims in the criminal sentencing process. Punishment is generally imposed on children who commit crimes, except serious crimes, by considering negotiations and alternative sanctions. This opinion is generally held by juvenile court judges and greatly influences decision making. As a country that is legally bound by the UN Convention on the Rights of the Child, Indonesia is obliged to protect children who are in conflict with the law. Law no. 11 of 2012 Juncto Law no. 3 of 1979 concerning Children's Courts is expected to be a control in law enforcement that protects children's rights.